Nilai Diagnostik Italian Score untuk Memprediksi Infeksi Bakteri Extended Spectrum Beta-Lactamase (ESBL) pada Pasien Sepsis di RSUP Dr. M. Djamil Padang - Fadrian, Fadrian; Ahmad, Armen; Khairat, Khairat (Jurnal Penyakit Dalam Indonesia, 2024)
Introduction. Infections caused by Extended-Spectrum Beta-Lactamase (ESBL) bacteria, especially in septic patients, require adequate management. Giving definitive antibiotics according to culture results takes a long time. Therefore, a clinical scoring system is needed to predict ESBL bacterial infection, one of which is the Italian score. Methods. This research used a cross-sectional design and was conducted in the inpatient room of RSUP Dr. M. Djamil Padang for 6 months. The samples in this study were septic patients who underwent culture examination at RSUP Dr. M. Djamil Padang who met the research inclusion and exclusion criteria. Sampling was carried out using consecutive sampling, and the total sample obtained was 34 samples. Selected samples will have an Italian score calculated, and specimens will be taken for clinical culture examination. Data analysis and processing will involve 2x2 tables and ROC curves. Results. Among a total of 34 participants with an equal distribution of male and female subjects (50% each), the average age was 59 years (standard deviation [SD] 14.15). Microbiological culture results revealed that 26 subjects (76.47%) were identified as positive for ESBL, while 8 subjects (23.53%) were classified as non-ESBL. Based on the Italian score, 22 patients were found to be ESBL-positive, and 12 were non-ESBL. The diagnostic performance of the Italian score yielded a sensitivity of 80.77%, specificity of 87.5%, positive predictive value (PPV) of 95.45%, and negative predictive value (NPV) of 58.33%. The accuracy of the Italian score in predicting ESBL bacterial infections among septic patients at RSUP Dr. M. Djamil Padang was demonstrated by an area under the curve (AUC) of 0.820 (95% confidence interval [CI] 0.75-1.00; p=0.002). Conclusion. The Italian score demonstrated significant performance as a tool in predicting the risk of ESBL bacterial infection.